Perception and use of reinforcement by special education teachers. Issue 4 (12th June 2017) - Dovey, Terence M.; Francis, Rebecca; Corbett, Shevon; Dibb, Bridget
Abstract : This study aimed to investigate whether special education teachers shared similar difficulties in their understanding of reward and punishment as their mainstream peers. Thirty‐five teachers working in six special education needs schools took part in a mixed methods study to explore their use and understanding of reinforcement principles. The purpose of the mixed methods approach was to triangulate the teachers use and perceived use of different reinforcement strategies within the classroom. Teachers' had a good grasp of positive reward‐based strategies, but their understanding of the other three types of reinforcement (negative reward, punishment and penalty) was less accurate. There was a clear aversion amongst the sample to discuss punishment with many stating that they do not use it, which contrasted with the observations. Structured continued professional development interventions are required to rectify the discrepancies between belief and evidence.